The efffect of two different conditions of whole-body vibration on flexibility and jumping performance on artistic gymnasts - Dallas, G.; Kirialanis, P. (Science of Gymnastics Journal, 2013)
The purpose of this study was to examine the effect of different conditions of Whole Bode Vibration (WBV) on flexibility and jumping performance on artistic gymnasts. Twelve well trained gymnasts volunteered to participate in this study. They were performed under two different condition protocols. The first was examined as WBV combined with static stretching condition (WBVSS) and the second was examined as WBV. Flexibility and explosive strength tests were performed initially (Pre), immediately after the intervention (Post 1), 15 minutes (Post 15) and 30 minutes after the end of the intervention program (Post 30). A two-way ANOVA (condition * trials) with repeated measures on both factors was used. The level of significance was set at p < 0.05. Univariate analyses with Bonferroni adjustments (0.05/6) were selected as post hoc tests. The results revealed no significant interaction between conditions and trials in all examined variables (p>0.05). However, significant difference was found with respect to Sit&Reach test between pre and post 1 measurement (p=0.002). Further, the percentage improvement of WBV was greater in SJ and CMJ variables compared to WBVSS condition. Conclusively, both conditions (WBVSS and WBV) were effective on flexibility and jumping performance on artistic gymnasts and that each of themhas a specific effect on the examined variables.